Bone Traumas Among the Skeletal Population from Gruczno (11-14 C.). - Kozłowski, Tomasz (Anthropological Review, 1993)
The analysis involved 1786 skeletons of individuals of different age and sex found at a site in Gruczno (Bydgoszcz voivodeship). Posttraumatic symptoms were observed macroscopically. In cases of uncertainty, X-ray pictures were used. The symptoms were found more frequently and were more diversified in men than in women. On skulls the changes were located most frequently on the frontal and parietal bones. As regards postcranial skeletons, analogous changes were most numerous on bones of upper and lower extremities. A general tendency of the number of injuries to increase with age was also detected. In men the largest increase occured between categories of age adultus and maturus, while in women it was greatest between maturus and senilis. The reason for this was probably a greater frequency of exposure of men to traumatogenous situations in this period, while in women it could be caused by a physiological factor, namely the climacteric.In the material single bone fractures and posttraumatic fusions of bones prevailed. Sprains, comminuted fractures, amputations, crushes and, in one case, a greenstick fracture were also detected. A small percentage of complications after bone fractures indicates the ability to heal them by immobilization of the limb.